Interpretation of The Impact of Industrialization on Education, Economy, and Culture in Jepara Regency - Muslimin, Khoirul; Mohammad, Gunawan; Darnoto, Darnoto (Widyagogik, 2024)
This article discusses the impact of industrialization in Jepara Regency, focusing on education, economy, and culture. The purpose of the research in this article is to identify the impact of industrialization, the factors that influence it, and how the Jepara community adapts to these changes. Through a descriptive quantitative approach, this study aims to provide scientific and practical contributions to the development of social sciences, especially anthropology, as well as to regional development, especially Jepara Regency. This article also discusses the background context of industrialization, the development of economic growth centers, and its impact on the arts, traditions, and lifestyles of the community. By exploring the basic concepts of industrialization and their relevance to Jepara Regency, this article provides in-depth insights into the industrial transformation in the region.